Intestinal Lymphatic Delivery of Praziquantel by Solid Lipid Nanoparticles: Formulation Design, In Vitro and In Vivo Studies - Mishra, Amit; Vuddanda, Parameswara Rao; Singh, Sanjay (Hindawi Publishing Corporation, 2014)
The aim of the present work was to design and develop Praziquantal (PZQ) loaded solid lipid nanoparticles (PZQ-SLN) to improve the oral bioavailability by targeting intestinal lymphatic system. PZQ is practically insoluble in water and exhibits extensive hepatic first-pass metabolism. PZQ SLN were composed of triglycerides, lecithin and various aqueous surfactants; were optimized using hot homogenization followed by ultrasonication method. The optimized SLN had particle size of 123 ± 3.41 nm, EE of 86.6 ± 5.72 %. The drug release of PZQ-SLN showed initial burst release followed by the sustained release. Inspite of zeta potential being around -10 mV, the optimized SLN were stable at storage conditions (5 ± 3 °C and 25 ± 2°C/ 60 ± 5 % RH) for six months. TEM study confirmed the almost spherical shape similar to the control formulations. Solid state characterization using differential scanning calorimeter (DSC) and powder X-ray diffraction (PXRD) analysis confirmed the homogeneous distribution of PZQ within the lipid matrix. The 5.81-fold increase in AUC 0 → ∞, after intraduodenal administration of PZQ-SLN in rats treated with saline in comparison to rats treated with cycloheximide (a blocker of intestinal lymphatic pathway), confirmed its intestinal lymphatic delivery. The experimental results indicate that SLN may offer a promising strategy for improving the therapeutic efficacy and reducing the dose.
Keywords: ntestinal lymphatic delivery; praziquantel; solid lipid nanoparticles; Formulation Design; In Vitro; In Vivo Studies